Phase II trial of bevacizumab and sorafenib in recurrent ovarian cancer patients with or without prior-bevacizumab treatment - Lee, Jung-Min (Gynecol Oncol, 2020)
OBJECTIVE: To examine whether blocking multiple points of the angiogenesis pathway by addition of sorafenib, a multi-kinase inhibitor against VEGFR2/3, Raf, c-Kit, and PDGFR, to bevacizumab would yield clinical activity in ovarian cancer (OvCa). METHODS: This phase II study tested bevacizumab plus sorafenib in two cohorts; bevacizumab-naïve and bevacizumab-exposed patients. Bevacizumab (5mg/kg IV every 2weeks) was given with sorafenib 200mg bid 5days-on/2days-off. The primary objective was response rate using a Simon two-stage optimal design. Progression-free survival (PFS) and toxicity were the secondary endpoints. Exploratory correlative studies included plasma cytokine concentrations, tissue proteomics and dynamic contrast-enhanced-magnetic resonance imaging (DCE-MRI). RESULTS: Between March 2007 and August 2012, 54 women were enrolled, 41 bevacizumab-naive and 13 bevacizumab-prior, with median 5 (2–9) and 6 (5–9) prior systemic therapies, respectively. Nine of 35 (26%) evaluable bevacizumab-naive patients attained partial responses (PR), and 18 had stable disease (SD)≥4 months. No responses were seen in the bevacizumab-prior group and 7 (54%) patients had SD≥4 months, including one exceptional responder with SD of 27 months. The overall median PFS was 5.5 months (95%CI: 4.0–6.8 months). Treatment-related grade 3/4 adverse events (≥5%) included hypertension (17/54 [31%]; grade 3 in 16 patients and grade 4 in one patient ) and venous thrombosis or pulmonary embolism (5/54 [9%]; grade 3 in 4 patients and grade 4 in one patient). Pretreatment low IL8 concentration was associated with PFS≥4 months (p=0.031). CONCLUSIONS: The bevacizumab and sorafenib combination did not meet the pre-specified primary endpoint although some clinical activity was seen in heavily-pretreated bevacizumab-naive OvCa patients with platinum-resistant disease. Anticipated class toxicities required close monitoring and dose modifications.